Chiral Acetylenic Sulfoxide in Organic Synthesis: Addition of Chiral Secondary Amines - Yan, Sujun; Lam, K. T.; Mo, K. T.; Wong, W. Y.; Chan, W. H.; Lee, Albert W.M. (Letters in Organic Chemistry, 2005)
Chiral secondary amines of the 3,4-dimethoxyphenylethyl and the tryptamine system were reacted with chiral acetylenic sulfoxides and achiral acetylenic sulfone. In the case of 3,4-dimethoxyphenylethyl amine, much improved diastereoselectivity (96 : 4) was observed as compared to the reaction of achiral secondary amine with chiral acetylenic sulfoxides.
Keywords: alkaloid synthesis